Wire mesh capped DRPS based bronchial dosimeter for personal inhalation dosimetry due to radon progeny. (1st June 2021) - Rout, R P; Mishra, R; Prajith, R; Jalaluddin, S; Sapra, B K
Abstract: A study has been carried out to experimentally determine the calibration factor (CF) of the passive bronchial dosimeter, which consists of a direct radon progeny sensor capped with a 100-wire mesh. First, the CF was determined in controlled environmental conditions simulated in a calibration chamber. With aerosol concentrations varying from 10 4 p cm −3 to 10 5 p cm −3 and relative humidity varying from 60% to 80% in the chamber, CF was observed to be nearly constant with an average value of (3.8 ± 0.5) × 10 −3 mSv tracks −1 cm 2 . Then, the CF was determined in real indoor environments in which it was again observed to be almost constant and the mean value was found to be (5.6 ± 0.1) × 10 −3 mSv tracks −1 cm 2 . Pooling all the data on CFs obtained under controlled conditions and in real indoor environments, a lognormal distribution of the CF was observed with a geometric mean and geometric standard deviation of 0.0052 mSv tracks −1 cm 2 and 1.28 respectively. The experimentally determined value of CF was found to be in close agreement with the theoretically estimated value, taking into consideration the unattached fraction of radon progeny. This dosimeter is passive, cheap, lightweight and, moreover, the CF being stable against environmental variations, will be useful in monitoring inhalation doses due to radon progeny for occupational workers.